The effect of destination image on revisit intention with memorable tourism experience (MTE) as intervening variable - Wiranti Tasia; Yasri Yasri (Marketing Management Studies, 2021)
The purpose of this research was to analyze: (1) The effect of destination image on memorable tourism experience, (2) The effect of destination image on revisit intention, (3) The effect of memorable tourism experience on revisit intention, (4) The effect of destination image on revisit intention through memorable tourism experience as a intervening variable or as a mediating variable. The type of this research is quantitative research. The population of this study were all tourism of Air Manis Beach with the numbers of samples in this study were 380 respondens. This study was analyze using SmartPLS 3.0. The result on this research indicate (1) There is a significant effect of Destination image on memorable tourism experience, (2) There is a significant effect of Destination image on revisit intention, (3) There is a significant effect of Memorable tourism experience on revisit intention, (4) There is a significant effect of Destination image on revisit intention through memorable tourism experience as a intervening variable or as a mediating variable.